Evolution of the Horizontal Winds in Jupiter's Great Red Spot From One Jovian Year of HST/WFC3 Maps. Issue 18 (27th September 2021) - Wong, Michael H.; Marcus, Philip S.; Simon, Amy A.; de Pater, Imke; Tollefson, Joshua W.; Asay‐Davis, Xylar
Abstract: We measured the horizontal winds in Jupiter's Great Red Spot (GRS) using data from the WFC3/UVIS instrument on board the Hubble Space Telescope (HST). The data cover 11 epochs from 2009 to 2020. Long‐term monotonic trends in size and shape previously noted from the visible cloud appearance are paralleled by changes in the high‐speed ring around the vortex. The circularization of the GRS cannot be explained by changes in the horizontal wind shear of the surrounding environment. The velocity fields suggest no long‐term trend in the static stability inside or outside the vortex. Instead, the changes are accompanied by a 4%–8% increase in the mean wind speeds of the high‐speed ring from 2009 to 2020. Changes in the wind field coincided with the South Equatorial Belt Outbreak storms of 2016–2017, but not with 2019 "flaking" events involving detachment of red material from the main oval. Plain Language Summary: We measured the horizontal winds in Jupiter's Great Red Spot (GRS) using data from the WFC3/UVIS instrument on board the Hubble Space Telescope (HST). The data cover 11 time periods from 2009 to 2020. Winds blow fastest in a high‐speed ring around the outside of the GRS. Previous pictures of the clouds showed that the GRS was shrinking and becoming more like a circle and less like an oval. We measure similar changes in the high‐speed ring. We rule out some possible causes for the changes: changes in the wind shear of the surrounding atmosphere, or changes in how temperature varies with height. As the GRS shrinks and circularizes, the average wind speed in the high‐speed ring gets faster. Some changes in the GRS wind patterns happened at the same time as a giant nearby storm in 2016/2017, but we did not find changes at the same time as flaking events in 2019. By "flaking" we mean pictures showing that small areas of red, normally kept inside the GRS, detached and blew away from the spot. Key Points: A high‐speed ring marking the edge of the Great Red Spot velocity field has been shrinking and circularizing at a roughly constant rate Mean wind speeds within the high‐speed ring have increased by 4%–8% from 2009 to 2020, at a roughly constant rate Velocity field changes coincided with a major 2016 storm, but we found no changes in 2019 when red material flaked away from the main oval